Near-Infrared Visual Differentiation in Normal and Abnormal Breast Using Hemoglobin Concentrations - Mehnati, Parinaz; Khorram, Sirous; Zakerhamidi, Mohammad Sadegh; Fahima, Farhood (Journal of Lasers in Medical Sciences, 2017)
Introduction: Near-infrared (NIR) optical imaging is a non-ionizing modality that is emerging as a diagnostic/prognostic tool for breast cancer according to NIR differentiation of hemoglobin (Hb)concentration. Methods: The transmission values of LED-sourced light at 625 nm were measured by power meter to evaluate the optical properties of Hb in breast phantom containing major and minor vessels. For the simulation of blood variations in cancerous breast condition, we prepared 2 concentrations of pre-menopausal Hb and 4 concentrations of post-menopausal Hb and, for comparison with normal tissue, one concentration of Hb injected inside the phantom’s vessels. Imaging procedure on the phantom was also conducted by LED source and CCD camera. The images from the experiments were compared with the results obtained from the images analyzed by MATLAB software. Finally, mammography of phantom including various concentration of Hb was prepared. Results: The transmitting intensities of NIR in blood containing 1, 2 and 4 concentrations of Hb in the major vessels were 52.83 ± 2.85, 43.00 ± 3.11 and 31.17 ± 2.27 μW, respectively, and in minor vessels containing similar Hb concentrations were 73.50 ± 2.43, 60.08 ± 5.09 and 42.42 ± 4.86 μW, respectively. The gray-scale levels on the major vessel were about 96, 124, 162 and on the minor vessel about 72, 100, 130 measured for 1, 2 and 4 Hb concentrations, respectively. The sensitivity and specificity of NIR imaging differentiation were 97.4% and 91.3%, respectively. Conclusion: Significant differences in transmitting intensity, optical imaging as well as software analysis of images were observed for 1, 2 and 4 concentrations of Hb in major and minor breast phantom vessels. Differentiation capability of minor vessels was higher than major vessels for Hb concentrations. Despite a good detection for location of vessels by mammography, it could not show differences between vessels with various concentrations. However, NIR optical imaging demonstrated a good image contrast for showing vessels in terms of concentration. This study recommends NIR optical imaging for prescreening breast cancer due to its potential for early diagnosis.